A study on the effect of grain dimension on the deformation of stent struts in tension, bending and unbending loading modes. (November 2016) - Abbaszadeh, M.; Kadkhodapour, J.; Schmauder, S.; Hoseinpour, M.
Abstract: Coronary stents are medical/mechanical micro devices which are used to open the arteries occluded by the build-up over time of fat, cholesterol, or other substances. A wide range of studies should be conducted on coronary stents since they play an important role in the health of patients who suffer from heart diseases. However, due to micro scale of these tools, and also their gripping and loading complexity during a test, it is very difficult to conduct experimental studies to understand their behavior. Moreover, because of their micro dimensions and subsequently, existence of only a few grains along their thickness, J2 flow theory is not appropriate to be implemented in order to define the mechanical behavior of such devices. Therefore, in this paper, 3D crystal plasticity finite element method (3D-CP-FEM) is used to understand the behavior of these devices. To achieve this goal and to find the hardening constants of strut, some simulations were designed and compared with an experimental study. Also, the effect of grain size in terms of w / d and l / d was investigated on the failure strain of struts under uniaxial tensile test. " w " and " l " are the width and length of the strut, respectively, and " d " is the average grain size. The results showed that failure strain increases within creasing w / d and decreasing l / d . Parameter waviness was used to measure the qualification of stent struts in bending and unbending simulations. Results revealed that the edges of strut are the critical areas and have more potential to failure. Additionally, it was found that with the increase in the w / d ratio, waviness decreases and the struts become homogeneous in behavior. Highlights: 3D crystal plasticity finite element method (3D-CP-FEM) was used to understand the behavior of stent struts. The effect of grain dimension on the deformation of struts in tension, bending and unbending loading modes was investigated. Since there are fewer grains in 2D model compared to 3D, 2D model predicts the macroscopic failure strain better than 3D. Decreasing the number of grains along the width of strut, the number of necking areas increased. Localization transferred from grain interior to grain boundaries by increasing the w/d ratios.